MicroRNA-1281 as a Novel Circulating Biomarker in Patients With Diabetic Retinopathy - Greco, Marta; Chiefari, Eusebio; Accattato, Francesca; Corigliano, Domenica M.; Arcidiacono, Biagio; Mirabelli, Maria; Liguori, Rossella; Brunetti, Francesco S.; Pullano, Salvatore A.; Scorcia, Vincenzo; Fiorillo, Antonino S.; Foti, Daniela P.; et al. (Frontiers in Endocrinology, 2020)
Objective: Recently, the role of circulating miRNAs as non-invasive biomarkers for the identification and monitoring of diabetes microvascular complications has emerged. Herein, we aimed to: identify circulating miRNAs differentially expressed in patients with and without diabetic retinopathy (DR); examine their predictive value; and understand their pathogenic impact. Methods: Pooled serum samples from randomly selected matched patients with type 2 diabetes, either with or without DR, were used for initial serum miRNA profiling. Validation of the most relevant miRNAs was thereafter conducted by RT-qPCR in an extended sample of patients with DR and matched controls. Results: Following miRNA profiling, 43 miRNAs were significantly up- or down-regulated in patients with DR compared with controls. After individual validation, 5 miRNAs were found significantly overexpressed in patients with DR. One of them, miR-1281, was the most up-regulated and appeared to be specifically related to DR. Furthermore, secreted levels of miR-1281 were increased in high glucose-cultured retinal cells, and there was evidence of a potential link between glucose-induced miR-1281 up-regulation and DR. Conclusion: Our findings suggest miR-1281 as a circulating biomarker of DR. Also, they highlight the pathogenic significance of miR-1281, providing insights for a new potential target in treating DR.